User satisfaction with m-government sites: an empirical investigation - Zamzami, Ikhlas F.; Mahmud, Murni (SSRN, 2014)
The rapid development of mobile sites and their continued use by users, as well as government organizations delivering their services to citizens has witnessed considerable high growth over the years. However, it appears that mobile services may lack quality and user satisfaction, since the sites are mostly developed and design without user involvement. This paper empirically investigates the context, content, and customization factors that influence user satisfaction of mobile sites. The context factor was evaluated based on menu structure, navigation, and aesthesis; the content factor was evaluated based on title and content area; the customization factor was evaluated based on screen and personalization. Overall, the paper examines the user perceptions on the quality of M-government mobile interface of three selected Ministry in KSA. An experiment was conducted among the M-government services users, thereafter, a questionnaire and brief interview was conducted to collected data for statistical analysis. A descriptive data analysis and Spearman rho correlations analysis was conducted to examine the relationships among the factors. The findings of the study suggest that there is a significant relationship between the factors of mobile context, content, and customization with user satisfaction. The findings also indicate that the quality of mobile interface services has a positive impact on user satisfaction. Finally, the model and empirical results provide valuable indicators for the direction of future research and also suggest guidelines for developing quality and usable mobile interface services that will successfully meet users’ needs and expectations.